PENGARUH HALAL AWARENESS DAN HALAL CERTIFICATION TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN MUSLIM (STUDI PADA RESTORAN SOLARIA SAGA SORONG) - ALFIYAH MEI SAPUTRI; RAIS DERA PUA RAWI; MITTA MUTHIA WANGSI, (Journal of Management and Accounting (JMA), 2025)
This study aims to determine the effect of halal awareness and halal certification on Muslim consumer purchasing decisions at Solaria Saga Sorong Restaurant. The type of research used is correlation with a quantitative approach. The sample in this study was 100 respondents with criteria set by the researcher. The sampling technique used purposive sampling. Data collection was carried out using primary data sources with questionnaires. Data analysis techniques using instrument tests, classical assumption tests, multiple regression analysis, and data hypothesis testing are processed using SPSS software version 25. The results in the study show that halal awareness has a positive and significant effect on Muslim consumer purchasing decisions at Solaria Saga Sorong Restaurant. Halal certification has a positive and significant effect on Muslim consumer purchasing decisions at Solaria Saga Sorong Restaurant. Independent variables, namely halal awareness and halal certification simultaneously or together, have a positive and significant effect on the dependent variable, namely Muslim consumer purchasing decisions at Solaria Saga Sorong Restaurant.